When life-saving measures leave a mark: Non-traumatic subperiosteal orbital hematoma after cardiopulmonary resuscitation - Yong Yuin Chong; Sylves Patrick; Joan Marie Palikat (Kugler Publications, 2025)
Subperiosteal orbital hemorrhage is rare, usually seen in young adult males following direct facial or orbital trauma. However, nontraumatic subperiosteal orbital hemorrhage (NTSOH) has been infrequently reported in association with sudden elevations in cranial venous pressure, venous congestion, bleeding diathesis, or paranasal sinusitis. Compressive optic neuropathy may ensue if it is missed or left untreated.